Association between blood manganese and cardiovascular diseases among U.S. adult population - Boxuan Pu (Scientific Reports)
Abstract Manganese (Mn) is a known toxicant and an essential trace element, and it plays an important role in various mechanisms in relation to cardiovascular health. However, epidemiological studies of the association between blood Mn and cardiovascular diseases (CVD) among U.S. adults are rare. A cross-sectional study of 12,061 participants aged ≥ 20 was conducted using data from the National Health and Nutrition Examination Survey 2011–2018. Logistic regression and restricted cubic spline were used to examine the relationship between blood Mn levels and total CVD risk and specific CVD subtypes. Bayesian kernel-machine regression (BKMR) and weighted quantile sum (WQS) analyses were performed to explore the joint effects of Mn with other metals on CVD. The results showed that individuals with the third quartile group of blood Mn levels had significantly lower risks of CVD, displaying a non-linear U-shaped dose-response relationship. A significant interaction of age on this association was observed. No significant associations were found between Mn levels and specific CVD subtypes. BKMR and WQS analyses showed a positive association between heavy metal mixtures and CVD risks, with no interaction between Mn and other metals. In conclusion, blood Mn levels were significantly associated with CVD risks with a U-shaped relationship in U.S. adults, with possible age-specific differences. Future larger prospective studies are warranted to validate these findings.